“You Help Us Tell our Story”: Making Inuvialuit Living Histories in Digital and Real Time - Gruben, Ethel-Jean; Piskor, Ashley; Joe, Mervin; Kotokak, Lena; Lyons, Natasha; Hodgetts, Lisa; Hennessy, Kate; Edgerton, Elizabeth; Stewart, David; Arnold, Charles; von Szombathyix, Chris; Lukuku, Jasmine (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2022)
Inuvialuit have always created culture through our/their living and land-based practices. For us, making culture means doing, practicing, and sharing activities and songs and country food, on the land and in town, together with our families and communities. These layers of history are embedded in the landscape of Inuvialuit Nunangat, our homeland, and in the voices of Elders past and present speaking about their knowledges and experiences. In this paper, we describe how Inuvialuit communities are practicing our living traditions today and capturing them using digital methods to produce a new Inuvialuit Living History website that celebrates the past, present, and future of our communities.